KEBIJAKAN FORMULASI HUKUM PIDANA DALAM PENANGGULANGAN TINDAK PIDANA PERJUDIAN MELALUI INTERNET (INTERNET GAMBLING) - Erwin Ubwarin (SASI, 2017)
the development of science and technology led to the development of society as well, but this development also has a negative side, in playing gambling conventional, the players and the city should meet at the gambling table or in the territory of a country's legal yet, gambling using the internet facilities, quite the player (user) and airports sitting in front of a computer desk and then accessing gambling sites and instantly be able to do gambling. Players and airports may not necessarily be in a country, but across the country or several countries, in the Book of Law Criminal Law, and Law Number 7 Year 1974 On Gambling Control does not regulate the act of gambling via the internet, on Law No. 11 Year 2008 on Information and Electronic Transactions, criminalize gambling via the internet, but only to ensnare the city is not against the player